THE USE OF LEARNERS’ DIARIES: DOES IT WORK TO ENGAGE STUDENTS’ METACOGNITION IN LEARNING IF CLAUSES? - Fidaniar Tiarsiwi (ELLTER Journal, 2021)
Metacognitive strategies are expected as ‘higher order executive skills’ which enable college students to approach learning systematically and effectively by using the elements of planning, monitoring and evaluating. This study is conducted to investigate whether or not metacognitive strategies can affect the development of structural knowledge of students. To reflect how the students use these strategies, learning diary can lead the learners to strategy use. Twenty-one participants of third semester students were involved. Nine of them were selected to be probed intensively for their metacognitive habits in learning If Clauses. Then, they were divided into three groups according to the level of students’ progress and their mid test score. The first group was assumed as novice learners, the second group was categorized as medium level students and the last group was presumed as expert learners. This study revealed that expert learners were better diarist in documenting what they did when learning. The medium level students also indicated that their capability in realizing the use of their cognition was up and down. They were good at evaluating their shortcoming and monitoring some progress, but they were poor at planning and modifying strategies. Meanwhile, the novice learners less reflected how they learned on their documentation. It could be illustrated that they did not have any motivation to plan their learning, evaluate and monitor their learning.